ОЛИЙ МАТЕМАТИКА ФАНИНИ ЛОЙИҲАЛАБ ЎҚИТИШНИНГ ЗАМОНАВИЙ КОНЦЕПЦИЯСИ УНИНГ МАТЕМАТИКА ЎҚИТУВЧИСИ ФАОЛИЯТИНИ ЛОЙИҲАЛАШДАГИ РОЛИ - Опаева, Г.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of the modern conception of teaching the subject «Higher Mathematics» by designing and the role and activity of Mathematics in this project work.